MXene/PVDF metacomposites with ultra-high and negative permittivity - Li Wei; Lv Fei; Hou Qing (EPJ Applied Metamaterials)
The dielectric behavior of MXene/polyvinylidene fluoride (PVDF) metacomposites, which simultaneously exhibit ultra-high dielectric constants and negative permittivity, has been investigated. The material exhibits a substantial enhancement in dielectric constant at low frequencies, with values reaching 105, which is primarily caused by interfacial polarization and the unique architecture of MXene. The composite transitions to negative permittivity with increasing MXene content, a result of conductive network formation and free electron accumulation at high filler levels. The dielectric response is highly morphology-dependent, with accordion-shaped formations producing Drude-type negative permittivity and clay-like formations showing Lorentz-type negative permittivity. These dual characteristics of ultra-high and negative permittivity make MXene/PVDF metacomposites highly promising for applications in advanced electronic devices, energy storage, and electromagnetic wave manipulation.